Estimates of Responsiveness, Minimally Important Differences, and Patient Acceptable Symptom State in Five Patient‐Reported Outcomes Measurement Information System Short Forms in Systemic Lupus Erythematosus. Issue 1 (4th December 2019) - Katz, Patricia; Pedro, Sofia; Alemao, Evo; Yazdany, Jinoos; Dall'Era, Maria; Trupin, Laura; Rush, Stephanie; Michaud, Kaleb
Abstract : Objective: Examinations of Patient‐Reported Outcomes Measurement Information System (PROMIS) measures in adult systemic lupus erythematosus (SLE) have provided support for their cross‐sectional validity in SLE. We estimated responsiveness to change, meaningful changes (minimally important differences [MIDs]), and the patient acceptable symptom state (PASS) for five PROMIS short forms to facilitate longitudinal use and interpretation of PROMIS scales in SLE. Methods: Data from five administrations of PROMIS short forms in the FORWARD SLE cohorts were used. Pearson correlation coefficients were used to assess associations between changes in PROMIS measures and changes in anchor measures for responsiveness analyses. Worse, same, or better groups were defined for each anchor. Differences in PROMIS scores were calculated for each consecutive PROMIS administration; mean changes in PROMIS scores of individuals in the worse, same, and better groups were calculated. Both anchor‐based and distribution‐based methods were used to estimate MIDs. PASS was defined as the 75th‐percentile positive score among those who considered their health to be acceptable or who were somewhat or very satisfied with their health. Results: All PROMIS short forms showed adequate responsiveness to changes in related patient‐reported outcomes. However, only the fatigue and pain interference scales were responsive to self‐reported SLE activity. Taking into account all methods, we estimated MIDs for each scale to be approximately two points. All PASS values were better than the population mean T‐score of 50. Conclusion: These results support use and further study of PROMIS short forms in SLE and should facilitate interpretation of PROMIS scores and changes.